Penerapan Aplikasi Sakti Dalam Pengelolaan Keuangan Di Badan Narkotika Nasional (BNN) Provinsi Sumatera - Rizki Nur Amalia Nasution; Juliana Nasution (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2022)
A recording system using an application is very much needed by agencies in carrying out financial management. A good recording system can produce well-structured financial reports so that the reporting is also structured. The purpose of this study was to find out about how the application of the SAKTI application in financial management at the BNNP of North Sumatra. The research method used in this research is a qualitative approach. Data were collected by using observation, interview, and literature study techniques. The results show that the application of the SAKTI at the National Narcotics Agency of North Sumatra Province began in early 2022, although it is still very new in its application, it is quite effective and optimal, but employees still need more knowledge so that its implementation can be more optimal